Determining Infected Aortic Aneurysm Treatment Using Focused Detection of Helicobacter cinaedi - Saito Jien; Rimbara Emiko; Inaguma Shingo; Hasegawa Chihiro; Kamiya Shinji; Mizuno Akihiro; Sone Yoshiaki; Ogawa Tatsuhito; Numata Yukihide; Takahashi Satoru; Asano Miki (Emerging Infectious Diseases, 2022)
We detected Helicobacter cinaedi in 4 of 10 patients with infected aortic aneurysms diagnosed using blood or tissue culture in Aichi, Japan, during September 2017–January 2021. Infected aortic aneurysms caused by H. cinaedi had a higher detection rate and better results after treatment than previously reported, without recurrent infection.